Penerapan Metode Single Exponential Smoothing Dalam Peramalan Penjualan Barang - Ginantra, Ni Luh Wiwik Sri Rahayu; Anandita, Ida Bagus Gede (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
The technology of buying and selling goods in managing goods in and out will provide convenience for the management in managing stock data, financial control and profit calculation that will be immediately known by stakeholders. Forecasting method is a method that is able to analyze several factors that are known to influence the occurrence of an event with a long grace period between the need for knowledge of an event to occur in the future and the time the event has occurred in the past. In a retail company, if this forecasting method is applied in the planning of goods management, the company will be assisted in the process of planning the sale of goods which is currently still being done by predicting the amount of sales of goods that will come without any calculation, causing excessive purchases of goods that can affect the stock of goods. Single exponential smoothing method is a development of the single moving averages method where the forecasting method is done by repeating calculations continuously using the latest data and each data is weighted. The single exponential smoothing method considers the weight of the previous data by giving weight to each data period to distinguish the priority of data. The single exponential smoothing method is a method used in short-term forecasting that is usually only 1 month ahead which assumes that the data fluctuates around a fixed mean value without consistent trends or growth patterns. The accuracy of the application of the single exponential method in forecasting sales of goods in this study with an alpha value of 0.1 on the MAPE calculation average is 2%.